P685 Improvement in patient-reported Inflammatory Bowel Disease Questionnaire outcomes, and relationship with disease activity, in tofacitinib-treated patients with ulcerative colitis: Data from the OCTAVE clinical trials. (25th January 2019) - Dubinsky, M C; Bressler, B; Armuzzi, A; Salese, L; DiBonaventura, M; Maller, E; Fan, H; Woodworth, D A; Su, C
Abstract: Background: Tofacitinib is an oral, small-molecule JAK inhibitor approved in several countries for the treatment of ulcerative colitis (UC). We assessed relationships between patient (pt)-reported Inflammatory Bowel Disease Questionnaire (IBDQ) outcomes and Mayo score (a widely used measure of clinical activity) in tofacitinib UC induction and maintenance studies. Methods: We analysed patients from two randomised, placebo-controlled, 8-week tofacitinib induction studies (OCTAVE Induction 1 and 2, NCT01465763 and NCT01458951) and a 52-week, randomised, placebo-controlled maintenance study (OCTAVE Sustain, NCT01458574). We evaluated IBDQ remission (total score ≥190) and response (≥30-point increase from baseline) at Week 8 (induction) and Weeks 24 and 52 (maintenance). These criteria are more stringent vs. previously reported IBDQ remission (total score ≥170) and response (≥16-point increase from baseline) thresholds. We evaluated relationships between IBDQ total scores and total Mayo scores at baseline and Week 8 (induction) and Weeks 24 and 52 (maintenance) using Spearman correlation. Results: In OCTAVE Induction 1 and 2, mean baseline IBDQ total score of each treatment ranged from 117.5 to 124.9. Statistically significant effects of treatment with tofacitinib 10 mg twice daily (BID) vs. placebo were observed at Week 8 for IBDQ remission ( p < 0.05) and response ( p < 0.0001) (Table 1). In OCTAVE Sustain, mean baseline IBDQ total score of each treatment ranged from 181.3 to 182.3. There were statistically significant maintenance treatment effects with 5 and 10 mg BID vs. placebo for IBDQ remission and response at Weeks 24 and 52 (all p < 0.0001; Table 2). Spearman correlation coefficients between IBDQ total score and total Mayo score in OCTAVE Induction 1 and 2 at Week 8 were −0.67 and −0.59, respectively. In OCTAVE Sustain, correlation coefficients were −0.57 at Week 24 and −0.40 at Week 52. Conclusions: For patients with moderate to severe UC, induction and maintenance therapy with tofacitinib resulted in statistically significant improvements in patient-reported quality of life vs. placebo, as measured using comparatively stringent IBDQ criteria. Moderate correlations between IBDQ and Mayo scores were observed from Week 8 in OCTAVE Induction to Week 52 in OCTAVE Sustain.